Sport-Specific Capacity to Use Elastic Energy in the Patellar and Achilles Tendons of Elite Athletes - Wiesinger, Hans-Peter; Rieder, Florian; Kösters, Alexander; Müller, Erich; Seynnes, Olivier R. (Frontiers in Physiology, 2017)
Introduction: During running and jumping activities, elastic energy is utilized to enhance muscle mechanical output and efficiency. However, training-induced variations in tendon spring-like properties remain under-investigated. The present work extends earlier findings on sport-specific profiles of tendon stiffness and cross-sectional area (CSA) to examine whether years of distinct loading patterns are reflected by tendons’ ability to store and return energy. Methods: Ultrasound scans were performed to examine the morphological features of knee extensor and plantar flexor muscle-tendon units in elite ski jumpers, distance runners, water polo players and sedentary controls. Tendon strain energy and hysteresis were measured with combined motion capture, ultrasonography and dynamometry. Results: Apart from the fractional muscle-to-tendon CSA ratio being lower in the knee extensors of ski jumpers (-31%) and runners (-33%) than in water polo players, no difference in the considered muscle-tendon unit morphological features was observed between groups. Similarly, no significant difference in tendon energy storage or energy return was detected between groups. In contrast, hysteresis was lower in the patellar tendon of ski jumpers (-33%) and runners (-30%) compared to controls, with a similar trend for the Achilles tendon (significant interaction effect and large effect sizes η2 = 0.2). Normalized to body mass, the recovered strain energy of the patellar tendon was ~50% higher in ski jumpers than in water polo players and controls. For the Achilles tendon, recovered strain energy was ~40% higher in ski jumpers and runners than in controls. Discussion: Advantageous mechanical properties related to tendon spring-like function are observed in elite athletes whose sport require effective utilization of elastic energy. However, the mechanisms underpinning the better tendon capacity of some athletes to retain elastic energy could not be ascribed to intrinsic or morphological features of the lower limb muscle-tendon unit.